Enhancing safe medication use in home care: insights from informal caregivers - Gil-Hernández, Eva; Ballester, Pura; Guilabert, Mercedes; Sánchez-García, Alicia; García-Torres, Daniel; Astier-Peña, María Pilar; Gea-Velázquez de Castro, María Teresa; Cobos-Vargas, Ángel; Pérez-Pérez, Pastora; Carrillo, Irene; Fernández-Navascués, Ana María; Mira, José Joaquín (Frontiers in Medicine, 2024)
Objectives To investigate the factors influencing medication errors made by informal caregivers while providing care at home. Methods A cross-sectional study based on an online survey, which included both structured and open-ended questions, was conducted in Spain. The survey comprised 49 questions to collect self-reported avoidable medication errors made by caregivers at home. Results A total of 685 caregivers participated in the survey, with 346 considered qualified (having received >20 h of training). On average, 13.5 (SD 38.2, 95% CI 10.5–16.5) errors per caregiver per year were self-reported. Errors were more prevalent among non-qualified caregivers, males, direct relatives of the care recipient, those with external occupations, or those who used external aids. Conclusion Errors made by informal caregivers occur more frequently than expected, and recognizing these errors remains a challenge. Training is essential for creating safer care environments by increasing awareness of error sources and the risks associated with medication. Recipients’ direct relatives should receive appropriate training, considering differences between male and female caregivers. Associations and companies within the care economy sector should prioritize the creation of safer home care environments as a key objective.